EFFECTIVENESS OF MUSICURE TO CONTROL PAIN IN BRONCHOSCOPY AT THE HOSPITAL DR. MOEWARDI SURAKARTA - Jayanti Revit; Wildan Ferdian; Debree Septiawan (Faculty of Medicine Universitas Kristen Duta Wacana, 2023)
Background Sampling in bronchoscopy can lead to acute consequences, such as intrabronchial bleeding, bronchospasm, and pneumothorax. Bronchoscopies make patients uneasy because they fear discomfort and difficulty breathing. Hypnotherapy, music therapy, and aromatherapy can help during bronchoscopies. Musicure is considered to assist people to grow well by sending